2020
DOI: 10.3390/app10248923
|View full text |Cite
|
Sign up to set email alerts
|

Modified Gingival Index (MGI) Classification Using Dental Selfies

Abstract: Background: Gum diseases are prevalent in a large proportion of the population worldwide. Unfortunately, most people do not follow a regular dental checkup schedule, and only seek treatment when experiencing acute pain. We aim to provide a system for classifying gum health status based on the MGI (Modified Gingival Index) score using dental selfies alone. Method: The input to our method is a manually cropped tooth image and the output is the MGI classification of gum health status. Our method consists of a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Patients who agreed to participate to the study were asked to fill in a questionnaire, according to Helsinki regulations. Age and days of hospitalization were recorded, together with the following periodontal and oral health indices, registered in the hospital ward with informed consent: Decayed Missing Filled Teeth (DMFT) [ 19 ], Plaque Index (PI) [ 20 ], and Modified Gingival Index [ 21 ]. The DMFT index was scored by summing up all teeth with restorations, teeth missing at the moment of the survey, and teeth with extensive carious process that would inevitably cause the loss of the tooth (the cause of loss of dental elements, due to caries or periodontal disease, was revealed following the medical history and interview with the patients).…”
Section: Methodsmentioning
confidence: 99%
“…Patients who agreed to participate to the study were asked to fill in a questionnaire, according to Helsinki regulations. Age and days of hospitalization were recorded, together with the following periodontal and oral health indices, registered in the hospital ward with informed consent: Decayed Missing Filled Teeth (DMFT) [ 19 ], Plaque Index (PI) [ 20 ], and Modified Gingival Index [ 21 ]. The DMFT index was scored by summing up all teeth with restorations, teeth missing at the moment of the survey, and teeth with extensive carious process that would inevitably cause the loss of the tooth (the cause of loss of dental elements, due to caries or periodontal disease, was revealed following the medical history and interview with the patients).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding clinical parameters, we chose the GI as a primary outcome objective, since (i) it was used in studies presenting beneficial effects of probiotics [ 45 , 46 , 86 88 ], (ii) it was considered the most common index used in preventive/ therapeutic clinical trials evaluating gingival inflammation [ 98 ], (iii) it has been supported by histological studies (high GI: infiltrated connective tissue) [ 99 ] and (iv) it provides more parameters than other gingival indices, e.g., BOP-Index solely determines the presence of bleeding [ 100 ] and the modified gingival index (MGI) uses only visual parameters [ 101 ], which is biased due to subjective measurements of color changes of the gingiva [ 98 ]. Regarding plaque accumulation, we will use the modified plaque index (MPI) [ 66 ], since it allows to describe the amount of plaque not only in approximal areas like the approximal plaque index (API) [ 61 ], but also on the cervical area and around the bracket since additional plaque retention niches need to be evaluated in orthodontic patients and since probiotics reduced plaque accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moncada et al [ 33 ] showed that calibration can restore the brightness, contrast, and color of images such that they match the actual clinical condition. Tobias et al [ 38 ] proposed a dental self-timer to accurately assess gingival health through photographs. The present study evaluated the gingival status of full-crown restorations, and there was high agreement between the camera-based assessment and clinical examination in the calibration group.…”
Section: Discussionmentioning
confidence: 99%